Aspectos do duplo em Orlando de Virginia Woolf e em Orlanda de Jacqueline Harpman - Vila Nova de Moraes Hazin, Marli (2003)
This study presents a comparative analysis between Virginia Woolf s Orlando and Jacqueline Harpman s Orlanda. It takes as a starting point the fact that Harpman houses Woolf s novel inside her own text and plays overtly with parody, citation, allusion, and mise en abyme, techniques which had already been used by Woolf. The analysis points out the way Harpman transcontextualizes the structural elements in Woolf s novel and reexamines questions that had been raised by Woolf almost seventy years ago. This research goes beyond the technical features to demonstrate that the heart of the matter may reside in human being s eagerness to be accepted as a multiple self, what leads the analysis into studying the mythical representations of the double. After demonstrating the way Harpman transcontextualizes the key elements in Woolf s novel, the analysis follows the itinerary of the double in both narratives, focusing primarily on Narcissus and the Androgyne and secondarily on other mythical figures like Apollo and Daphne